2004
DOI: 10.1016/s1097-2765(03)00505-7
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for Autoinhibition of FLT3 by the Juxtamembrane Domain

Abstract: FLT3 is a type III receptor tyrosine kinase that is thought to play a key role in hematopoiesis. Certain classes of FLT3 mutations cause constitutively activated forms of the receptor that are found in significant numbers of patients with acute myelogenous leukemia (AML). The mutations occur either in the activation loop, for example, as point mutations of Asp835 or as internal tandem duplication (ITD) sequences in the juxtamembrane (JM) domain. To further understand the nature of FLT3 autoinhibition and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
372
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(395 citation statements)
references
References 50 publications
6
372
0
4
Order By: Relevance
“…The structure of the FLT3 kinase in its autoinhibited state was recently elucidated 24 and allowed us to ask whether this might reveal a mechanism by which mutation of N841 could lead to the 24 Residues highlighted by this study are indicated and are shown in "stick" representation. Y572 is at the N-terminal residue of the JM domain visible in the crystal structure.…”
Section: Resultsmentioning
confidence: 97%
“…The structure of the FLT3 kinase in its autoinhibited state was recently elucidated 24 and allowed us to ask whether this might reveal a mechanism by which mutation of N841 could lead to the 24 Residues highlighted by this study are indicated and are shown in "stick" representation. Y572 is at the N-terminal residue of the JM domain visible in the crystal structure.…”
Section: Resultsmentioning
confidence: 97%
“…The two activating mutations act through two distinctively different mechanisms. The FLT3-ITD mutation activates the kinase activity through releasing the negative constraint that the juxtamembrane region poses on the kinase domain of FLT3 [15]. Thus, the mutation does not involve any structural changes in the kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…The ITD occurs as an in-frame duplication of a sequence of varying length, leading to release of the negative regulatory constraint that the juxtamembrane domain poses on the kinase domain of FLT3 [15,16]. This is found in about 17-26% of patients with AML, and is the most common mutation in FLT3 [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…24 The ITD disrupts the autoinhibitory function of the juxtamembrane domain, resulting in constitutive autophosphorylation of FLT3 and activation of its downstream effectors. 25,26 The FLT3-ITD mutation produces growth factor-independent proliferation in leukemia cell lines and a fatal myeloproliferative syndrome in murine models. 27 Interestingly, however, when FLT3-ITD was expressed in cells from knockout mice lacking FLT3 ligand, the receptor was only weakly activated.…”
Section: Flt3 Mutationsmentioning
confidence: 99%